Conversion Within Islam: Becoming Shia in Majority Sunni in Indonesia - Imran, Imran; Syamsiyatun, Siti; Sofjan, Dicky (Universitas Islam Indonesia, 2023)
Since the Iranian Islamic Revolution in 1979, Shia and its community have been the subject of much research. This paper examines the phenomenon of conversion from Sunni to Shia in Indonesia. It seeks to identify the reasons people choose to convert to Shia, even though it can lead to psychological, economic, social, and political tensions. This is a qualitative research based on a fieldwork conducted in four cities in Indonesia, namely Jakarta, Bandung, Yogyakarta and Makassar. These cities are representative of Indonesia. The results of the study show that there are at least four 'gates' that are commonly cited as reasons for converting from Sunni to Shia. These gates are philosophy, history, irfan/sufism, and fiqh. The typology of encounters through the four gates is a strong typology that we found in our research. Most people who convert from Sunni to Shia usually pass through one or several gates that are key factors in their decision to accept Shia.